The Depiction of African American Women in Suzan-Lori Parks’ In the Blood - Snoor Ismael Mahmood; Saman Hussein Omar (Zanco Journal of Humanity Sciences)
African American women are depicted in various stereotypes that are well-known to the American public. They are perceived from others’ perspectives in various historical and literary discourses. This paper scrutinizes the characterization of Hester, in Parks’s In the Blood, as an unmarried woman with five fatherless children, as a no-count, hussy, and slut.  Using Patricia Hill Collins’ ideas, mainly her arguments in her book Black Feminist Thought, the study delineates the purpose behind the creation of Hester as a slut. Parks demonstrates that Black women are more likely to be abused because of their racial and sexual identities, which are socially constructed to maintain the dominance of the powerful group and to uphold black cultural inferiority.  She claims that because of their socioeconomic status, they are more likely to be sexually abused and objectified. She thus challenges the stereotype of African American women as slut, hypersexual, and indolent welfare queens.